POLSKA, KTÓREJ NIE MA (BORIS AKUNIN, DOKĄD PŁYNIEMY?, LATAJĄCY SŁOŃ) - Zywert, Aleksandra (Acta Neophilologica, 2019)
This paper focuses on the image of Poland in the times of partitions as presented in the works by Boris Akunin on the basis of the stories entitled Where Shall We Go? andThe Flying Elephant. This image is created with the use of space (as well as sensory) mapping through the presence of toponyms, names of dishes considered to be typically Polish (the geography of taste), interweaving the text with Polonisms and (sometimes spelled in the Latin alphabet) Polish words, Polish surnames, references to religious and national stereotypes. Despite its entertaining convention (the collage of action and detective novels enriched with some elements of steampunk) the image of Poland sketched in the analyzed works is relatively credible and devoid of superpower pathos. Akunin does not exaggerate and balances the proportions between type and stereotype by dint of showing that the official political area does not reflect the real lives of coexisting communities.